Cardiac abnormalities and exercise tolerance in patients receiving renal replacement therapy. Issue 6457 (1st December 1984) - Bullock, R E; Amer, H A; Simpson, I; Ward, M K; Hall, R J
Abstract : The exercise tolerance of the survivors of a consecutive group of 100 patients in a renal dialysis and transplant programme was compared with the prevalence of cardiac abnormalities detected by exercise testing, echocardiography, and radionuclide angiography. Fifty four patients attended for investigation 27 (SD 7) months after starting renal replacement therapy. Forty three of them (80%) were receiving antihypertensive treatment. Their performance on a bicycle ergometer exercise test was compared with that of 62 normal subjects and the patients divided into five groups of decreasing ability. The exercise tolerance of the patients was very poor, only 17 performing within the normal range. Impairment in exercise capacity was not explained by the type or quality of renal replacement therapy. Fourteen patients developed ischaemic electrocardiographic changes on exercise. Left ventricular ejection fraction was assessed by gated blood pool scanning in 37 patients; all nine of the patients with an abnormally low radionuclide ejection fraction also had abnormal exercise tolerance. Satisfactory M mode echocardiograms were obtained from 45 of the patients, and only two were normal. Left ventricular hypertrophy was detected in 25 (56%) of the echocardiograms, and abnormalities indicating impaired left ventricular function were common and widespread. Grouping all the abnormal cardiac features together for the patients in each exercise group showed a striking linear trend of increasing proportion of cardiac abnormalities with worsening exercise tolerance among the five exercise groups (p less than 0.001). The proportion of patients becoming unemployed within one year of starting renal replacement therapy similarly increased, from nil to 60% from the best exercise group to the most incapacitated. Twenty nine of the original cohort of 100 patients subsequently died, cardiovascular disease accounting for 12 (41%) of these deaths. Diminished exercise tolerance in patients receiving renal replacement therapy is strongly associated with cardiac abnormalities and reduced employment prospects.